Алтан хадны бичээс: Урьдчилсан судалгаа - Ц. Баттулга (Acta Mongolica, 2005)
There is an ancient runic inscription at the winter camp named Altan Khad which is located in the northwest 15 km far from Biger soum in Gobi-Altai province. There are 2 rows of superficial runic scripts as well as very many tantra scripts that were written by Mongolian and Tibetan. The inscription consists of 2 parts and it was carved on the smooth large rock which is on the top of the winter camp.